Integration of acoustic and electric hearing is better in the same ear than across ears - Fu, Qian-Jie; Galvin, John J.; Wang, Xiaosong (Scientific reports, 2017)
Advances in cochlear implant (CI) technology allow for acoustic and electric hearing to be combined within the same ear (electric-acoustic stimulation, or EAS) and/or across ears (bimodal listening). Integration efficiency (IE; the ratio between observed and predicted performance for acoustic-electric hearing) can be used to estimate how well acoustic and electric hearing are combined. The goal of this study was to evaluate factors that affect IE in EAS and bimodal listening. Vowel recognition was measured in normal-hearing subjects listening to simulations of unimodal, EAS, and bimodal listening. The input/output frequency range for acoustic hearing was 0.1–0.6 kHz. For CI simulations, the output frequency range was 1.2–8.0 kHz to simulate a shallow insertion depth and the input frequency range was varied to provide increasing amounts of speech information and tonotopic mismatch. Performance was best when acoustic and electric hearing was combined in the same ear. IE was significantly better for EAS than for bimodal listening; IE was sensitive to tonotopic mismatch for EAS, but not for bimodal listening. These simulation results suggest acoustic and electric hearing may be more effectively and efficiently combined within rather than across ears, and that tonotopic mismatch should be minimized to maximize the benefit of acoustic-electric hearing, especially for EAS.